Antropologia a nauki stosowane. Antropologia polska nadchodzących lat - Drozdowski, Zbigniew (Polskie Towarzystwo Antropologiczne, 1986)
An analysis and evaluation has been made of the present investigation directions of the Polish anthropology, world tendencies of the development of this discipline and the expected social needs. This permitted to divide the main directions of anthropological studies into the following ones: 1) In the field of methods and investigation techniques we can expect the implementation of different methods of the investigation on biochemical properties of the human organism, different internal organs in vivo (radiological and tomographic techniques), and also sociometric techniques. A further computerization will follow both in the process of the accumulation of anthropological information data and their processing. 2) Onthogenetic studies will be concentrated around the problem of biological value of Polish population and its conditioning by the changing environmental factors. More intensive investigation will be carried out on the productivity period of human life and the senile period with a wider consideration of the functional properties. Studies on biological conditionings and results of different phenomena in the individual development process of man will be extended. 3) Studies on the morphofunctional conditionings of the physical activity of man will be developed. Investigations in this field should supply information about biosocial prerequisites of the matching and selection in different forms of motor activity of man, both the professional and those connected with different fields of physical culture. It creates the basis of compensating activity, particularly compensating the negative results. 4) The traditional Polish studies in the field of ethnical anthropology will be more and more concentrated around the problem of the biology of the prehistoric populations and the process of ethnogenesis. They should lead to the understanding of the structure of the extinct populations and their living conditions, the cognition of the microevolutional transformations of man, and also their conditionings. It will permit a reconstruction of the living environment of our ancestors, their mode of living and on this background of the biological transformations of population. 5) Studies on the philogenesis of man will probably still move in the direction of general theory of anthropogenesis with the utilization of the investigation methods characteristic of Polish anthropology. 6) In the field of the practical application of anthropology we should expect a continuation or undertaking of studies on: a) developmental norms both of the somatic features and the physiological and motoric features, b) cyclical expertises referring to the biological conditions of population, c) periodical verification of the standards of clothes and other equipment of mass consumption, d) sporadical expertises on different biosocial situations in the regional populations in connection with the growing ecological endangerment.
Anthropology and applied sciences. Polish anthropology of the Coming years